THE EFFECT OF THE NUMBERED HEADS TOGETHER MODEL BASED ON MIND MAPPING ON STUDENT LEARNING OUTCOMES IN MAN 3 LANGKAT - Rahayu, Sri; Elfrida, Elfrida; Pandia, Ekariana S (Jurnal Biologi Sains dan Kependidikan, 2024)
This research was motivated by the decline in students' abilities and grades and the teaching and learning process carried out was still less effective because after several semesters the learning process was online. So to improve it, an efficient learning model is needed which is expected to improve students' learning abilities and values. This research aims to determine student learning outcomes using the Numbered Heads Together learning model based on Mind Mapping in class X IPA MAN 3 Langkat, to determine the effect of the Numbered Heads Together learning model based on Mind Mapping on student learning outcomes in class X IPA MAN 3 Langkat. This type of research is quantitative research and uses an experimental design, that is true experimetal design. The population in this study were all MAN 3 Langkat students. And the samples in this research were 36 students in class X IPA 2 as the experimental class and 36 students in class X IPA 3 as the control class. The results of this research show that there is an influence of the numbered heads together model based on mind mapping on student learning outcomes in ecosystem material at MAN 3 Langkat where tcount ttable, namely 5.999 1.994. Based on the research results, it can be concluded that the numbered heads together model based on mind mapping has an influence on student learning outcomes in ecosystem material at MAN 3 Langkat. Through the numbered heads together model based on mind mapping, the student learning outcomes in the experimental class were 85.78 in the good category and the learning outcomes in the control class were 73.5 in the sufficient category.